EKSPLORASI ETNOMATEMATIKA PADA KERAJINAN CAPING DI DAERAH KABUBATEN KAMPAR - Hidayat, Rizki; Ediputra, Kasman; Zulhendri, Zulhendri; Rizki, Lussy Midani; Hidayat, Adityawarman (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Mathematical concepts are often used in everyday life. The term that refers to mathematical concepts in cultural concepts is ethnomathematics. Ethnomathematics is a science used to understand how mathematics is adapted from a culture. This research discusses the exploration of ethnomathematics contained in the process of making Caping crafts in Kampar Regency. This research aims to explore the ethnomathematics concept found in Caping crafts in Kampar Regency. This type of research is qualitative with data collection obtained from observation, documentation and interviews related to Caping crafts in Kampar Regency. The results of the research show that: The mathematical concept that exists in the Caping making process is the geometry of flat shapes, namely equilateral triangles, circles and rectangles. The geometric shape of a space is a cone. Transformation geometry is reflection.